Meeting tourism: an approach from the perspective of its residents in the case of Mar del Plata, Argentina (2020-2023) - Mastrandrea, Aldana (2023)
Introduction: Meeting tourism has acquired a growing interest, due to its growth prospects and the benefits it provides to residents; so that the efforts made by the localities to position themselves as a host destination are notable. The city of Mar del Plata has extensive experience and track record in organizing meetings. However, it is necessary to investigate the knowledge that they have about this modality. Objetive: Analyze the perception of the residents of the town of Mar del Plata about meeting tourism, in order to deepen the design of successful tourism planning and management. Method and technique: Given the mixed nature of the research, a theoretical-methodological perspective based on the geography of perception is adopted. The perception of the residents of Mar del Plata about meeting tourism is analyzed. Observation, the application of questionnaires and semi-structured interviews with key informants were used, as well as the use of primary and secondary information sources. Results: It is evident that the residents of Mar del Plata know the characteristics and potential of meeting tourism and, given their degree of commitment, interest and involvement with this modality, promote a positive assessment of the town. [Continue reading in the article]